SARS-CoV-2 infection among employees working from home and on site: An occupational study in Switzerland - Schmid, Alexia; Anker, Daniela; Dubois, Julie; Bureau-Franz, Isabelle; Piccardi, Nathalie; Colombo Mottaz, Sara; Cullati, Stéphane; Chiolero, Arnaud; Rodondi, Pierre-Yves (Frontiers in Public Health, 2022)
During the COVID-19 pandemic, many companies implemented working from home to mitigate the spread of the disease among their employees. Using data from Corona Immunitas Nestlé, a seroepidemiological study conducted among employees from two Nestlé sites in Switzerland, we aimed to investigate whether there was a difference in SARS-CoV-2 infection rates between employees working most of the time from home and employees mobilized in a workplace equipped with a specialized occupational safety unit and strict sanitary measures. We also investigated whether this association was modified by household size, living with children, vulnerability, worries about an infection, and worries about adverse health consequences if infected. Data were collected between December 8, 2020, and February 11, 2021. Previous SARS-CoV-2 infections were ascertained by the presence of anti-SARS-CoV-2 IgG antibodies in the blood. Of the 425 employees included (53% women; mean age 42 years ranging between 21 and 64 years), 37% worked most of the time from home in 2020 and 16% had been infected with SARS-CoV-2. Participants who worked most of the time from home in 2020 had slightly higher odds of being infected with SARS-CoV-2 compared to participants who never or only sometimes worked from home (adjusted OR 1.29, 95% CI 0.73-2.27). The association was stronger in participants living alone or with one other person (adjusted OR 2.62, 95% CI 1.13-6.25). Among participants living with two or more other persons (adjusted OR 0.66, 95% CI 0.30-1.39) and among vulnerable participants (adjusted OR 0.53, 95% CI 0.13-1.93), working from home tended to be associated with lower odds of infection. In conclusion, in a context of strict sanitary measures implemented in the workplace, employees working from home did not seem to be at lower risk of infection compared to those working on site, especially those living alone or with one other person.